CORRELATION OF MATERNAL SERUM 25 HYDROXY VITAMIN D WITH NEWBORN ANTHROPOMETRY - Muhammad Iqbal; Yusrawati Yusrawati; Hudila Rifa Karmia; Joserizal Serudji (Universitas Andalas, 2024)
Vitamin D deficiency (VDD) is identified as a public health problem in many countries, and pregnant women have been identified as a high-risk group, among whom the prevalence of VDD ranges between 20 and 40%. Vitamin D deficiency causes essential health problems, not only in the mother but also in the baby, because the mother's vitamin D stores are the primary source of vitamin D for the fetus. During pregnancy, severe vitamin D deficiency in mothers has been associated with biochemical evidence of impaired bone homeostasis, congenital rickets, and bone fractures in newborns. This study aims to determine the correlation between umbilical cord blood 25(OH)D levels in term pregnancy and Neonatal anthropometry. This research is analytical research using a cross-sectional approach. The sample in this study amounted to 40 people. Data analysts use people tests. The results of this study obtained an average umbilical cord serum 25(OH)D level of 14.70 Â± 4.93. There was no correlation between umbilical cord blood 25(OH)D levels in term pregnancy and neonate anthropometry (p>0.05). The average level of 25(OH)D is included in the insufficiency category. Therefore, it is necessary to increase vitamin D supplementation during pregnancy.